2017
DOI: 10.1097/gme.0000000000000786
|View full text |Cite
|
Sign up to set email alerts
|

The REJOICE trial: a phase 3 randomized, controlled trial evaluating the safety and efficacy of a novel vaginal estradiol soft-gel capsule for symptomatic vulvar and vaginal atrophy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
96
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 24 publications
5
96
1
3
Order By: Relevance
“…The study design for the REJOICE trial has been previously reported. 5 Women were randomized 1:1:1:1 to 4-, 10-, and 25- μ g TX-004HR or placebo. 5 Women self-administered 1 capsule per day intravaginally for 2 weeks, followed by bi-weekly dosing (3 to 4 days apart) for 10 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study design for the REJOICE trial has been previously reported. 5 Women were randomized 1:1:1:1 to 4-, 10-, and 25- μ g TX-004HR or placebo. 5 Women self-administered 1 capsule per day intravaginally for 2 weeks, followed by bi-weekly dosing (3 to 4 days apart) for 10 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…5 Women were randomized 1:1:1:1 to 4-, 10-, and 25- μ g TX-004HR or placebo. 5 Women self-administered 1 capsule per day intravaginally for 2 weeks, followed by bi-weekly dosing (3 to 4 days apart) for 10 weeks. 5 Changes from baseline to week 12 in the percentages of superficial cells and parabasal cells, vaginal pH, and severity of the patient-reported MBS of moderate-to-severe dyspareunia were measured as co-primary endpoints.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations